Electrophysiological properties and seizure networks in hypothalamic hamartoma. Issue 5 (16th April 2020) - Wang, Di; Shan, Yongzhi; Bartolomei, Fabrice; Kahane, Philippe; An, Yang; Li, Muyang; Zhang, Huaqiang; Fan, Xiaotong; Ou, Siqi; Yang, Yanfeng; Wei, Penghu; Lu, Chao; et al.
Abstract: Objective: Little is known about the intrinsic electrophysiological properties of hypothalamic hamartoma (HH) in vivo and seizure network since only few cases using stereoelectroencephalography (SEEG) electrodes exploring both cortex and HH have been published. To elucidate these issues, we analyzed simultaneous SEEG recordings in HH and cortex systematically. Methods: We retrospectively investigated data from 15 consecutive patients with SEEG electrodes into the HH for the treatment purpose of radiofrequency thermocoagulation treatment. Additional SEEG electrodes were placed into the cortex in 11 patients to assess extra‐HH involvement. Interictal discharges within the HH and anatomo‐electroclinical correlations during seizures of each patient were qualitatively and quantitatively analyzed. Results: Overall, 77 electrodes with 719 contacts were implanted, and 33 spontaneous seizures were recorded during long‐term SEEG monitoring. Interictally, distinct electrophysiological patterns, including isolated intermittent spikes/sharp waves, burst spike and wave trains, paroxysmal fast discharges, periodic discharges, and high‐frequency oscillations, were identified within the HH. Notably, synchronized or independent interictal discharges in the cortex were observed. Regarding the ictal discharges, the electrical onset pattern within the HH always started with abrupt giant shifts superimposed on low‐voltage fast activity across patients. The gelastic seizure network mainly involved the HH, orbitofrontal areas, and cingulate gyrus. Seizures with automatisms and impaired awareness primarily propagated to mesial temporal lobes. Moreover, independent ictal discharges arising from the mesial temporal lobe were detected in three out of nine patients. Interpretation: This study comprehensively reveals intrinsic electrophysiological patterns and epileptogenic networks in vivo, providing new insights into the mechanisms underlying cortical and subcortical epileptogenesis.